Русский язык как иностранный: элементарный уровень: учебное пособие - Михалева Е. В. Елена Владимировна; Майер А. К. Артур Карлович; Фрицлер А. А. Александр Александрович; Ярица Л. И. Людмила Ивановна; Шевелева С. И. Светлана Игоревна; Рустамова А. С. Анна Сергеевна (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана